HSP10 as a Chaperone for Neurodegenerative Amyloid Fibrils - Larsson, Johan N. K.; Nyström, Sofie; Hammarström, Per (Frontiers in Neuroscience, 2022)
Neurodegenerative diseases (NDs) are associated with accumulated misfolded proteins (MPs). MPs oligomerize and form multiple forms of amyloid fibril polymorphs that dictate fibril propagation and cellular dysfunction. Protein misfolding processes that impair protein homeostasis are implicated in onset and progression of NDs. A wide variety of molecular chaperones safeguard the cell from MP accumulation. A rather overlooked molecular chaperone is HSP10, known as a co-chaperone for HSP60. Due to the ubiquitous presence in human tissues and protein overabundance compared to HSP60 we studied how HSP10 alone influence fibril formation in vitro of Alzheimer’s disease associated Aβ1-42. At sub-stoichiometric concentrations eucaryotic HSP10s (human and Drosophila) significantly influenced the fibril formation process and the fibril structure of Aβ1-42, more so than the procaryotic HSP10 GroES. Similar effects were observed for prion disease associated prion protein HuPrP90-231. Paradoxically, for a chaperone, low concentrations of HSP10 appeared to promote fibril nucleation by shortened lag-phases which were chaperone and substrate dependent. Higher concentrations of chaperone while still sub-stoichiometric extended the nucleation and/or the elongation phase. We hypothesize that HSP10 by means of its seven mobile loops provides the chaperone with high avidity binding to amyloid fibril ends. The preserved sequence of the edge of the mobile loop GGIM(V)L (29-33 human numbering) normally dock to the HSP60 apical domain. Interestingly this segment shows sequence similarity to amyloidogenic core segments of Aβ1-42, GGVVI (37-41) and HuPrP90-231 GGYML (126-130) likely allowing efficient competitive binding to fibrillar conformations of these MPs. Our results propose that HSP10 can function as an important molecular chaperone in human proteostasis in NDs.